Manufacture and Photoelectrical Characterization of Poly(3-decylthiophene) Thin Films by Drop Casting Technique - Riga Junior, Luiz A. [UNESP]; Riga, Maria V. [UNESP]; Santos, Amanda M.P. [UNESP]; Medina, Maria E.R.S. [UNESP]; Borro, Marcelo S. [UNESP]; Simõis, André V.S. [UNESP]; Olivati, Clarissa A. [UNESP] (FapUNIFESP (SciELO), 2024)
Poly(3-decylthiophene) is a polymer with conductive characteristics due to its conjugated polymeric chain. With the search for new applications and improvements of these materials, in sensors, and OPVs, there is a great demand for deeper knowledge about them. This work aims to characterize the P3DT, through analysis of optoelectrical measurements. Using the drop casting technique, thin films were made onto solid substrates. The films were subjected to optical characterization by UV-Vis and optical microscopy. The electrical characterization was obtained by IxV curves and then measuring the photoconductivity through Ixt curves, with a solar simulator. With UV-Vis measurements, it was observed that the absorption of light in the visible spectrum reached a peak of 520 nm in the film, blue-shifted in the solution attributed to the differences in the organization of the polymer chains. The optical microscopy measurements indicate the formation of aggregates with a higher concentration of aggregates observed for the film obtained with a more concentrated solution. Finally, the photoconductivity measurements carried out obtained a positive response to the photo-excitation of the material due to exposure to light, with an increase in current in the film as the photo-exposure cycles were repeated.
Keywords: Chloroform; Drop casting; Optoelectronic properties